2003
DOI: 10.1007/s00520-004-0626-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of brief pain education on hospitalized cancer patients with moderate to severe pain

Abstract: The purpose of this randomized controlled study was to assess the effects of a structured pain education program on the pain experience of hospitalized cancer patients. Eligible cancer pain patients were randomly assigned to either an experimental group (receiving pain education 10-15 min per day for 5 days, n = 15) or a standard care control group (n = 15). The effects of the intervention on six pain-related variables were evaluated using three instruments. Pain intensity, pain interference with daily life, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
109
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(113 citation statements)
references
References 33 publications
(57 reference statements)
1
109
1
2
Order By: Relevance
“…Also, we should also consider the twoweek New Year's holidays in Iran straight after intervention and the possibility that some patients might not be able to do their exercises because of holiday trips and usual visits to their relatives' houses. Our findings are consistent with some previous studies on the effect of pain management educational programs for reducing pain intensity in patients with cancer [8].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Also, we should also consider the twoweek New Year's holidays in Iran straight after intervention and the possibility that some patients might not be able to do their exercises because of holiday trips and usual visits to their relatives' houses. Our findings are consistent with some previous studies on the effect of pain management educational programs for reducing pain intensity in patients with cancer [8].…”
Section: Discussionsupporting
confidence: 93%
“…Lai et al [8] found that after 5 days of pain management education for hospital admitted patients with cancer, had a significant reduction in their mean main, current pain, worst pain, and least pain scores in the case group compared to the control group. However, in the control group only the current pain and mean pain scores reduced significantly [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the interventions that were made in the studies, 5 (26.3%) evaluated Educational Programs, which include the implementation of scales and other features that allow a better assessment and management of pain [11,13,15,17,19]; 2 (10.5%) implemented evidence-based educational interventions, which include focus groups and application of guidelines with the professionals [18,20]; 2 (10.5%) applied cognitive-behavioral interventions, with a focus on understanding the nature of symptoms and improving the ability to control the symptoms [14,16]; and 1 (5.2%) applied daily pain management journals [12]. Table 2 highlights the main outcomes related to the studies included in the review.…”
Section: Health Education (N=10)mentioning
confidence: 99%